FACTORS AFFECTING THE ACCEPTANCE OF MOBILE PAYMENT SYSTEMS IN JORDAN: THE MODERATING ROLE OF TRUST - Manaf Al-Okaily; Mohd Shaari Abd Rahman; Azwadi Ali (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2019)
Nowadays, the smartphone applications play a critical role in every aspect of our life, as in the case of Jordan Mobile Payment (JoMoPay) system that can be used to save time, effort and money. Despite the immense benefits of JoMoPay system services, their acceptance by users in Jordan is very low. Moreover, the related issues of JoMoPay system has not been addressed substantially in the Jordanian context. In this respect, the research model proposed in this paper seeks to synthesize the extended Unified Theory of Acceptance and Use of Technology (UTAUT2) model variables namely; Performance Expectancy (PE), Effort Expectancy (EE), Social Influence (SI), Peer Influence (PI), Facilitating Conditions (FC), Hedonic Motivation (HM), Price Value (PV) and Habit (HT) as immediate predictors of intentions of users to accept JoMoPay system. In addition, to join new variables namely; Trust (TR) as the moderating effect among them.